Enhancing Children's Motor Skills through Clay Media at SD IT Al-Fajar - Olivine Alifaprilina Supriadi; Irfan Dwi Rahadianto; Tiara Radinska Deanda (Pascasarjana Universitas Mataram, 2026)
This community service project addresses the critical need for holistic education and physical-motor development at SD IT Al-Fajar Bandung. Modern educational trends often prioritize cognitive outcomes at the expense of physical and aesthetic dimensions, leading to a neglect of essential motoric skills in primary school children. Utilizing clay as a tactile and flexible medium, this program aimed to stimulate fine motor coordination among 50 elementary students. The intervention was designed within a holistic-integrative framework, combining creative art activities with Islamic core values such as Ihsan (excellence) and Amanah (trustworthiness). The workshop followed a structured pedagogical approach, beginning with university-led demonstrations of fundamental shapes and transitioning into autonomous creative exploration. Results indicated that the